The role of ISR disclosure as moderator the relationship between profitability and leverage towards corporate value - Reni Susanti; Imanda Firmantyas Putri Pertiwi (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2019)
The purpose of this research is to find out the role of ISR disclosure as a moderator of the relationship between profitability and leverage on firm value in companies listed in JII for the 2014-2018 period. This research uses quantitative research using Moderated Regression Analysis (MRA). This study uses secondary data in the form of panel data on companies registered in JII for the 2014-2018 period. The populations in this study are all companies registered in JII during the 2014-2018 period. The sampling method is carried out by purposive sampling by using several criteria to obtain 15 companies used as research samples. The results of this study indicate that profitability and leverage affect the value of the company. The results of the Moderated Regression Analysis (MRA) analysis show that disclosure of the ISR is able to moderate the relationship between profitability and firm value but towards the negative. However, ISR disclosure is not able to moderate the relationship between leverage and firm value.